2018
DOI: 10.1016/j.jviromet.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Development of a strand-specific RT-PCR to detect the positive sense replicative strand of Soybean blotchy mosaic virus

Abstract: Soybean blotchy mosaic virus (SbBMV), a plant virus of the genus Cytorhabdovirus is an economically important virus of soybean reported only from the warmer, lower-lying soybean production areas in South Africa. The virus consistently appears in soybean crops annually in spite of the absence of soybean plants in winter. One possible reason for this may be that the virus replicates and hence persists in the SbBMV vector, a leafhopper, Peragallia caboverdensis. RNA viruses with antisense genomes as inferred for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells13030226/s1, Figure S1: Expression analysis using a peak annotation pipeline; Figure S2: Protein blots for Figure 6B; Figure S3: Mitochondrial dsRNA; Table S1: Primers for dsRNA sensors; Table S2: Statistics of RNA sequencing data. References [3,[59][60][61][62]…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells13030226/s1, Figure S1: Expression analysis using a peak annotation pipeline; Figure S2: Protein blots for Figure 6B; Figure S3: Mitochondrial dsRNA; Table S1: Primers for dsRNA sensors; Table S2: Statistics of RNA sequencing data. References [3,[59][60][61][62]…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Negative-sense CiLV-C viral genomes detected in mite extracts ( Roy et al, 2015 ) could have been remnants from the infected plant cells after mite feeding ( Tassi et al, 2017 ). Moreover, the specific detection of the viral negative-strand RNA by reverse transcription-polymerase chain reaction (RT-PCR) could have been the result of false amplification due to either self-priming of the positive-strand RNA or the primer activity of other cellular nucleic acids ( Haddad et al, 2007 ; Boncristiani et al, 2009 ; Haist et al, 2015 ; Strydom and Pietersen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that priming RT with gene-specific primer (GSP) for a particular transcript would generate cDNA only from that desired RNA template and guarantee the specificity of signal in subsequent amplification by PCR. However, the conventional notion regarding absolute requirement of the exogenous primers during RT has been refuted by several reports involving detection of plant [1,2], animal [3][4][5] and human viruses [6,7] as well as expression of genes in eukaryotes [6][7][8][9], in which it was observed that cDNAs can be synthesized even without adding exogenous primers to the RT reaction. Generation of such nonspecific cDNAs through a primer independent mechanism has been linked to self-priming activity of the RNA template by its own 3 end [6] and previously termed as background priming [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the problem of background priming in RT-PCR, a multitude of approaches have been adopted at various stages, such as additional processing of sample RNA, variations at the level of cDNA synthesis and PCR amplification after RT [1][2][3][5][6][7][8][9][10][11][12]. These strategies include elimination of free nucleic acid contaminants from the RNA sample that can act as endogenous primers, RNase-Hmediated digestion of nontarget RNA strand, performing RT at a higher extension temperature, addition of DMSO to RT reaction, use of a thermostable reverse transcriptase, using reverse transcriptase with RNase-H activity and using one-step RT-PCR kits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation